2009
DOI: 10.1152/ajpheart.00272.2009
|View full text |Cite
|
Sign up to set email alerts
|

Region-specific adaptations in determinants of rat skeletal muscle oxygenation to chronic hypoxia

Abstract: Chronic exposure to hypoxia is associated with muscle atrophy (i.e., a reduction in muscle fiber cross-sectional area), reduced oxidative capacity, and capillary growth. It is controversial whether these changes are muscle and fiber type specific. We hypothesized that different regions of the same muscle would also respond differently to chronic hypoxia. To investigate this, we compared the deep (oxidative) and superficial (glycolytic) region of the plantaris muscle of eight male rats exposed to 4 wk of hypoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 77 publications
4
40
0
Order By: Relevance
“…Experiments using intrathecal fentanyl in humans during cycling have shown that opioid-mediated muscle afferents inhibit central motor drive (Amann et al, 2009;Gagnon et al, 2012); thus changes in afferent discharge with fatigue or oxygenation are expected to alter the pattern of muscle activation. Although a comparative analysis of the metabolic responses of the different portions of the quadriceps muscle in man has not been performed, rodent studies have shown that the metabolic response to hypoxia are region specific, depending on the predominant muscle fiber type and the degree of capillarization (Wust et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Experiments using intrathecal fentanyl in humans during cycling have shown that opioid-mediated muscle afferents inhibit central motor drive (Amann et al, 2009;Gagnon et al, 2012); thus changes in afferent discharge with fatigue or oxygenation are expected to alter the pattern of muscle activation. Although a comparative analysis of the metabolic responses of the different portions of the quadriceps muscle in man has not been performed, rodent studies have shown that the metabolic response to hypoxia are region specific, depending on the predominant muscle fiber type and the degree of capillarization (Wust et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The SDH activity in individual muscle fibers in histological sections was determined as described previously (55). Sections were incubated at 37°C in the dark for 20 min in a medium consisting of 37 mM sodium phosphate buffer pH 7.6, containing 74 mM sodium succinate and 0.4 mM tetranitroblue tetrazolium (TNBT).…”
Section: Methodsmentioning
confidence: 99%
“…However, an alternative view is that atrophy in large, type II, fibers may be protective against developing an anoxic core (and, hence, cell damage) under conditions where local capillary blood flow (and O 2 delivery) is reduced (24) or in hypoxia (55); whereas hypoxic/anoxic cell damage might be more prevalent following only small reductions in capillary contacts in highly oxidative, type I, fibers. The interaction between fiber size, capillarity and mitochondrial volume density is, therefore, far more complex than whole-muscle averages suggest (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle has the capacity to adapt to sustained hypoxia by way of modulation of skeletal muscle vasculature [1,2], muscle enzyme activities [3][4][5][6], muscle fibre size and distribution [7][8][9][10] and contractile performance [11][12][13]. Moreover, sustained hypoxia has been shown to elicit functional plasticity in respiratory muscles [9,10] in a manner that differs from the phenotypic changes occurring in limb muscles [10,14,15].…”
Section: Introductionmentioning
confidence: 99%